A dual-excited and dual near-infrared emission phosphor Mg14Ge5O24:Cr3+, Cr4+ with a super broad band for biological detection. Issue 1 (10th December 2020) - Wang, Xuejiao; Wang, Zhijun; Zheng, Mingjie; Cui, Jia; Yao Yao,; Cao, Lingwei; Zhang, Mengya; Yang, Zhibin; Suo, Hao; Li, Panlai
Abstract : Broadband near infrared phosphors with selective excitation and selective emission for biological detection. Abstract : Recently, near-infrared phosphors that can be applied in many fields such as night vision, agriculture, and bio-applications have attracted considerable interest in the research field worldwide. Herein, a multi-functional and dual-excited near-infrared phosphor Mg14 Ge5 O24 :Cr 3+, Cr 4+ which provides two emission bands ranging from 700 nm to 1100 nm and 1100 nm to 1700 nm has been obtained via the traditional high-temperature solid state reaction. The presence of six and four coordination ions in the olivine structure of Mg14 Ge5 O24 provides a favorable environment for the coexistence of Cr 3+ and Cr 4+ . Under blue light excitation, a super broad emission band ranging from 650 nm to 1100 nm with a full-width at half maximum (FWHM) of 266 nm is assigned to the spin-allowed 4 T2 (4F) → 4 A2 transition of Cr 3+ in a weak crystal-field environment. With the increase in the concentration of Cr ions, more and more Cr 4+ preferentially occupies four coordinated Ge 4+ sites, and the other broad emission band ranging from 1100 nm to 1600 nm with a FWHM of 256 nm that comes from the 3 T2 → 3 A2 transition of Cr 4+ is observed. The phenomenon of NIR I region excitation and NIR II region emission appears. The transmission experiment of a biological tissue proves that the Mg14 Ge5 O24 :Cr 3+, Cr 4+ phosphor has potential applications in the field of near-infrared light-emitting diodes for biological detection.